2014
DOI: 10.1200/jco.2013.52.0924
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Study of Mogamulizumab (KW-0761), a Defucosylated Anti-CC Chemokine Receptor 4 Antibody, in Patients With Relapsed Peripheral T-Cell Lymphoma and Cutaneous T-Cell Lymphoma

Abstract: Mogamulizumab exhibited clinically meaningful antitumor activity in patients with relapsed PTCL and CTCL, with an acceptable toxicity profile. Further investigation of mogamulizumab for treatment of T-cell lymphoma is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
211
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(231 citation statements)
references
References 39 publications
16
211
1
3
Order By: Relevance
“…C-C chemokine receptor 4 (CCR4) is expressed on NKTL and might be a suitable target for the antibody therapy. Because CCR4 is a receptor of CCL22 that activates Treg as discussed above, CCR4-targeted therapy would damage both CCR4-positive NKTL cells and Treg with manageable adverse events [70]. Indeed, we have shown that mogamulizumab, a defucosylated anti-CCR4 antibody, enhances the killing of NKTL cells by normal NK cells via antibody-dependent cell-mediated cytotoxicity [17].…”
Section: Antibody Therapiesmentioning
confidence: 78%
“…C-C chemokine receptor 4 (CCR4) is expressed on NKTL and might be a suitable target for the antibody therapy. Because CCR4 is a receptor of CCL22 that activates Treg as discussed above, CCR4-targeted therapy would damage both CCR4-positive NKTL cells and Treg with manageable adverse events [70]. Indeed, we have shown that mogamulizumab, a defucosylated anti-CCR4 antibody, enhances the killing of NKTL cells by normal NK cells via antibody-dependent cell-mediated cytotoxicity [17].…”
Section: Antibody Therapiesmentioning
confidence: 78%
“…A phase 2 study of mogamulizumab (1.0 mg/kg) in Japanese patients with CCR4-positive PTCL and CTCL has been recently reported. 32 This study enrolled a small number of CTCL patients (n 5 8) with only relapsed disease. However, the ORR of 35% was similar to the rate of 36.8% among the 38 patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mogamulizumab is a defucosylated and humanized monoclonal antibody to CCR4 that shows marked effects against ATL (12) and peripheral T-cell lymphoma (13). It works directly by depleting tumor cells and indirectly by increasing antitumor immunity through eTreg depletion via antibody-dependent cellular cytotoxicity (3).…”
Section: Introductionmentioning
confidence: 99%